GINI DP 6: Income Inequality and Participation: A Comparison of 24 European Countries - Bram Lancee
Previous research suggests that where inequality is high, participation is low. Two arguments are generally put forward to explain this finding: First, inequality depresses participation because people have diverging statuses and therefore fewer opportunities to share common goals. Second, people may participate more in social and civic life when they have more resources to do so. However, up till now, these explanations have been lumped together in empirical analyses. Using EU-SILC data for 24 European countries, we analyse how inequality in different parts of the income distribution is related to civic, cultural and social participation. Results indicate that a substantial part of the impact of inequality manifests itself through resources at the individual and societal level. However, independent of resources, it is still the case that higher inequality magnifies the relationship between income and participation. This is in line with a view that inter-individual processes explain why inequality diminishes participation.